(untitled) (The Strategic Review for Southern Africa, 2020)
The South African Parliament has since 1994 actively participated in formal, informal, and ad hoc bilateral parliamentary diplomacy. Through the analysis of this form of diplomacy, this article explores practical examples of Parliament’s bilateral international participation to ascertain the impact thereof on the state’s soft power capacity. Joseph Nye (2008; 2011)’s soft power tool of attraction is used as the theoretical lens through which these examples are assessed. Supplementary insights from parliamentary officials and confidential interviews with selected Members of Parliament who consistently participate internationally enriched the analysis. The article presents evidence of parliament’s soft power of attraction among foreign legislative and executive actors, but also identifies challenges that hinder strategic soft power successes. As South Africa’s bilateral parliamentary diplomacy continues to evolve, these findings provide insights on the role of Parliament as an international actor, as well as the need for the strategic positioning of bilateral parliamentary diplomacy within the state’s overall diplomatic practice for policymakers and foreign policy stakeholders to consider.